A357 Alloy by LPBF for Industry Applications - Lorusso, Massimo (Materials (Basel), 2020)
The aim of this study is to define the process parameters to build components for industrial applications in A357 alloy by Laser Powder Bed Fusion (LPBF) and to evaluate the effects of post-processing heat treatments on the microstructure and mechanical properties in order to obtain the highest hardness and strength. First, process parameters values were defined to obtain full dense components with highest productivity. Then samples were built for microstructural, hardness, and tensile strength investigation in different conditions: as-built, after a stress-relieving treatment, and after a T6 precipitation hardening treatment. For this latest treatment, different time and temperatures for solution and ageing were investigated to find the best in terms of final hardness achievable. It is demonstrated that samples in A357 alloy can be successfully fabricated by LPBF with a density of 99.9% and a mean hardness value achievable of 116 HV0.1, in as-built condition. However, for production purposes, it is fundamental to reduce the residual stresses typical of LPBF. It was shown that a similar hardness value could be obtained after a stress-relieving treatment followed by a proper T6 treatment, together with a coarser but more isotropic microstructure.